RELEVANSI PELARANGAN RIBA DALAM AL-QUR’AN TERHADAP PERSOALAN KONTEMPORER - Raihan Putri (Jurnal Syariah dan Ekonomi Islam, 2023)
Developments from time to time are increasing rapidly. Problems arising from the pattern of development of people's lives are increasing. One of the things related to muamalah that is regulated in the Al-Qur'an is the verse relating to usury. In this research, the author used several methods, both data collection methods, such as primary and secondary data, as well as methods for analyzing data, namely thematic and deductive analysis. The results of the research show that Hasby ash-Shidiqy is of the view that people who consume usury do not stand up, but stand like the person who was slammed by the devil. Meanwhile, Quraish Shihab is of the view that the content of the verse not only prohibits the practice of usury, but also strongly criticizes the perpetrators, even threatening them. Hasby ash-Shidiqy and Quraish Shihab both believe that usury during the Jahiliyyah era, known as usury nasi'ah, was usury which was clearly forbidden by Allah SWT. The prohibition of usury in the Koran has relevance to the movement of the real sector in the economy. This is because an economy based on usury will automatically ignore the underlying transactions which are the basis of the real sector.